The R-Functions Method in the Creep and Creep Damage Problems of Piecewise-Homogeneous Bodies of Revolution With Meridional Section of Any Shape - Sklepus, S. N. (NTU "KhPI", 2016)
We consider the axisymmetric problem of creep and creep damage for piecewise-homogeneous bodies of revolution with meridional section of any shape. We develop a method for the solution of the nonlinear initial boundary-value problem based on the combined application of the R -functions method and the Runge- Kutta- Merson method. The structures of the solution for the main types of boundary conditions are constructed. We present an example of calculation of creep, creep damage and long-term strength for a two-layer cylinder.
Keywords: piecewise-homogeneous body; creep; creep-induced damage; R-functions method